Barriers and facilitators to implement oral health policies on Brazil, Colombia, and Chile. (30th September 2020) - Lopes Galante, M; Lugo, D; Castro, G; Ovalle, M; Pischel, N; Giraldes, A; Carrer, F
Abstract: Background: Public health policies are important for the general population's well-being. Among the policies, oral health is included in the context of integral health, so those responsible for creating oral health policies and programs are key elements for the programs focusing on improving the health of a country's population. Oral health is considered a right to the citizen in the countries of this study (Brazil, Colombia and Chile), although their health systems are different. The aim of this study was to understand which barriers and facilitator occurs during the implementation of oral health programs/policies. Methods: A qualitative study was conducted within personal interviews with decision-makers, at the political, technical and academic levels. Data were transcribed and analyzed using Maxqda®. Results: It was observed that, at the moment of the insertion of oral health into the Health System, the formation of dentists with an emphasis in the public service proved to be a critical knot in these countries, also populatiońs lack of knowledge about their rights was mentioned. In Chile and Colombia one of the main facilitators was the previous existence of oral health programs. As barriers, we identified the lack of systematization of epidemiological data. In Brazil, the main facilitators were a large number of dentists already available in the job market and the political will of politicians to include oral health as public, mainly by the president of the country. Managers unprepared to work in public service was one of the main barriers. Conclusions: During the development and implementation of public policies several factors are encountered, and although oral health is offered in different ways by health systems, it can be concluded that human resources are fundamental elements for functioning of public services and consequently success, besides the interest of the managers and politicians for the inclusion of this theme in the political agenda of the country. Key messages: Oral health policies are influenced by several factors at the moment of its implementation, among them, the most prominent one is the formation of the dentist. Stakeholders should keep in mind that oral health is a fundamental part of the comprehensive health of the population and should include and advocate for this theme.